2002
DOI: 10.1073/pnas.152088999
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of the coloration mechanism in lobster shell: β-Crustacyanin at 3.2-Å resolution

Abstract: The binding of the carotenoid astaxanthin (AXT) in the protein multimacromolecular complex crustacyanin (CR) is responsible for the blue coloration of lobster shell. The structural basis of the bathochromic shift mechanism has long been elusive. A change in color occurs from the orange red of the unbound dilute AXT (max 472 nm in hexane), the well-known color of cooked lobster, to slate blue in the protein-bound live lobster state (max 632 nm in CR). Intriguingly, extracted CR becomes red on dehydration and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
240
2
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(263 citation statements)
references
References 32 publications
7
240
2
6
Order By: Relevance
“…It was proposed that α-crustacyanin consists of two groups of homologous proteins (CRTC, containing apoproteins C 1 , C 2 and A 1 , and CRTA, containing apoproteins A 2 and A 3 ) [43]. Cianci et al 2002 further reported the structural basis of the bathochromic shift and binding behavior based on subunits A 1 and A 3 of curstacyanin protein and several different perturbations of the carotenoid molecules [44].…”
Section: Invertebrate Carotenoid-binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that α-crustacyanin consists of two groups of homologous proteins (CRTC, containing apoproteins C 1 , C 2 and A 1 , and CRTA, containing apoproteins A 2 and A 3 ) [43]. Cianci et al 2002 further reported the structural basis of the bathochromic shift and binding behavior based on subunits A 1 and A 3 of curstacyanin protein and several different perturbations of the carotenoid molecules [44].…”
Section: Invertebrate Carotenoid-binding Proteinsmentioning
confidence: 99%
“…The absorption spectrum of the carotenoid astaxanthin along with the β-crustacyanins displays a bathochromic shift of 100 nm (λ max = 580 nm [40]. It was proposed that extension of conjugation by coplanarization of the β-ionone rings with the polyene chain and polarization resulting from hydrogen bonding at the C(4) and C(4′) keto groups of astaxanthin may be mainly responsible for the bathochromic shift [30,44].…”
Section: Invertebrate Carotenoid-binding Proteinsmentioning
confidence: 99%
“…A paradigm for a modular assembly of carotenoid-containing subunits into distinct holoproteins occurs in crustacyanin, isolated from lobster carapace. Various combinations of five b-crustacyanin subunits (each 20 kDa) combine to form dimers in which two carotenoids span the interface [31].…”
Section: The Red Carotenoid Proteinmentioning
confidence: 99%
“…For example, carotenoprotein crustacyanin, a well studied blue pigment from the lobster shell, contains orange carotenoid astaxanthin, which demonstrates a strong bathochromic shift due to noncovalent binding to a protein of lipocalin family (2).…”
mentioning
confidence: 99%